The Concept and Components of Engagement in Different Domains Applied to eHealth: A Systematic Scoping Review - Kelders, Saskia M.; van Zyl, Llewellyn Ellardus; Ludden, Geke D. S. (Frontiers in Psychology, 2020)
Background: Within the context of eHealth interventions, a shared understanding of what constitutes engagement is missing. A better understanding of engagement in and with eHealth technologies could provide a starting point for guidelines relating to the design and development of eHealth technologies. The aim of this systematic literature review is to gain a better understanding of: in what domains the concept of engagement features; what constitutes engagement in these different domains; and to determine whether there are any common components that seem to be important. Methods: A comprehensive literature search was conducted in the following bibliographic databases: Scopus, Web of Science, ScienceDirect, PsychInfo and ACM Digital Library. The databases were queried with a combination of the terms ‘engagement’ AND ‘concept OR theory OR definition’ occurring in the title of published, peer reviewed articles. For each included paper, the definition of engagement which was used and whether engagement was said to consist of multiple components, and what these components were, was extracted. Results: The search yielded 1231 unique titles. After title, abstract and full text screening, 69 articles were included. We categorized the papers into seven domains of engagement: student (n = 18), customer (n = 12), health (n = 11), society (n = 10), work (n = 9), digital (n= 8), and transdisciplinary (n = 1). It seems that some domains are more mature regarding their conceptualization and theorizing on engagement than others. Looking at the common components of engagement in the different domains, behavior, cognition and affect are seen most prominently. Conclusion: Although engagement is a much-disputed concept in many domains, it is foremost seen as a state of being engaged in something, which is part of the larger process of engagement. Behavior, cognition and affect are important components of engagement that may be specified for each context.